Do women managers keep firms out of trouble? Evidence from corporate litigation and policies - Adhikari, Binay K.; Agrawal, Anup; Malm, James (Journal of Accounting and Economics, 2019)
We find that firms where women have more power in the top management team, measured by female executives’ plurality and pay slice, face fewer operations-related lawsuits. This effect is robust to several treatments of endogeneity and does not appear to be driven by female executives' greater willingness to settle the cases. Evidence from a simultaneous equations approach suggests that firms where women executives have more power avoid lawsuits partly by avoiding some risky but value-increasing firm policies, such as more aggressive R&D, intensive advertising, and policies inimical to other parties.